The role of a smile in customer–employee interactions: Primitive emotional contagion and its boundary conditions - Verena Hofmann; Nicola E. Stokburger-Sauer; Martin Wetzels (Psychology & Marketing, 2024)
By investigating emotional contagion in customer–employee interactions using the emotional facial action coding system, this study offers a means to separate primitive emotional contagion from its conscious counterpart. As an empirical validation of primitive emotional contagion and its impact on customer satisfaction, the multifaceted research approach, involving an experimental laboratory study and two field studies in hospitality and retail settings, reveals consistent findings. Additionally, the influence of emotional contagion on customer satisfaction is moderated by the esthetic appeal of the interior design. This work advances the theoretical understanding of the dynamics of primitive emotional contagion; it also offers practical insights regarding the importance of interior designs and busyness for enhancing service interactions.
Keywords: 650; customer–employee interactions; customer satisfaction; emotional contagion; emotional facial action coding system (EMFACS); interior design; store busyness